Student perspectives toward pre-service teachers competencies - Adri, Junil; Ambiyar, Ambiyar; Refdinal, Refdinal; Verawardina, Unung; Efrianova, Vivi; Tanjung, Abrar; Ferdiansyah, Ferdiyansyah; Prima, Fani Keprila (Universitas Negeri Padang, 2020)
This study aims to determine how students' perceptions of the competence of prospective teachers in the PPLK program at SMK Negeri 1 Padang. Aspects that are observed in basic educational competencies are pedagogic, personality, professional, and social. This research is descriptive research. Observations were made for three years. The population in the study were all class X students of SMK Negeri 1 Padang. Sampling was done using random sampling technique using Slovin's formula. The findings of the study showed that the average competency of prospective teachers in the PPLK program at SMK Negeri 1 Padang for three years of observation was in a good category. The research findings recommend that there is a need for improvement in the pedagogical and social fields of prospective teachers. Teacher readiness to teach will affect the achievement of learning objectives. In addition, social competence is needed to establish communication and interaction between prospective teachers and teachers in schools and students. There needs to be an improvement in learning related to teaching preparation for prospective teachers specifically to emphasize pedagogic and social competencies